Indonesia's Strategic Role in The Development of International Law in The ASEAN Community - Mery, Lisa; Wulandari, Andi Sri Rezky; Patawari, Patawari; Nurmiati, Nurmiati (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The purpose of this study is explicitly to analyze Indonesia's strategic role in the development of International Law in the ASEAN Community and to understand Indonesia's contribution since the beginning of the formation and development of ASEAN, Indonesia when analyzed its role is significant because during the ASEAN leadership in certain years (1976, 2003, 2011 and 2023) this is very fundamental, where Indonesia's strategic efforts to continue to strengthen ASEAN as a unity in the Southeast Asian region that is growing rapidly, inclusive and sustainable, that the ASEAN Community has the capacity to resolve problems between member countries through the mechanism of International Law. Normative research methods are used to analyze the various strategies used in Indonesia's interactions as a country and part of the ASEAN community. Indonesia sees the opportunities in the ASEAN region as a space that can support Indonesian cooperation. Indonesia's success in including maritime issues in the ASEAN agenda is also an initial step that will help pave the way for Indonesia to realize its vision of the World Maritime Axis. Indonesia's significant role certainly promotes stability and security in the ASEAN Southeast Asia Region and it is important to remember Indonesia's commitment to the principles of International Law and peaceful resolution of disputes.